Reviews of Science for Science Librarians: Clinical Neuropsychology. Issue 2 (3rd April 2022) - Stankus, Tony
ABSTRACT: Today medical imagers can pinpoint the location of brain tumors and chart how far stroke damage has spread. However, there is another important, if less well-publicized profession – clinical neuropsychology – which develops, administers, and interprets diagnostic tests that allow for the assessment of the real-world consequences of these brain lesions and advises if there are prospects for remediation.